Epsilon Systems on Geometric Crystals of Type An - Nakashima, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We introduce an epsilon system on a geometric crystal of type An, which is a certain set of rational functions with some nice properties. We shall show that it is equipped with a product structure and that it is invariant under the action of tropical R maps.